Mengkaji Keterlibatan Motivasi Dalam Peningkatan Karir Pelaut - Oktyasari Putri, Candra; Hermawati, Renny; Khamdilah, Ali (Majalah Ilmiah Gema Maritim, 2023)
The purpose of this study is to examine the role of motivation in improving the career of seafarers. Efforts to answer these problems were carried out by research that recruited eight active seafarers as research resource persons. The research was conducted using a qualitative research method with a semi-structured interview approach. Furthermore, interview data were reviewed and further investigated. The study's results stated that the motivation of seafarers who came from themselves, family support, and the shipping company where they worked contributed to their desire to improve their careers. A high seafarer motivation will lead to a high career advancement for the seafarers, while a weak seafarer motivation will cause a weak career advancement.